Current Status of Septic Cardiomyopathy: Basic Science and Clinical Progress - Lin, Huan; Wang, Wenting; Lee, Madeline; Meng, Qinghe; Ren, Hongsheng (Frontiers in Pharmacology, 2020)
Septic cardiomyopathy is a complication that is sepsis-associated cardiovascular failure. In the last few decades, there is progress in diagnosis and treatment despite the lack of consistent diagnostic criteria. According to current studies, several hypotheses about pathogenic mechanisms have been revealed to elucidate the pathophysiological characteristics of septic cardiomyopathy. The objective of this manuscript is to review literature from the past 5 years to provide an overview of current knowledge on pathogenesis, diagnosis and treatment in septic cardiomyopathy. Keywords: Sepsis, Heart failure, Septic cardiomyopathy, Pathogenesis, Treatment, Diagnosis, Left ventricular ejection fraction (LVEF).